Discovering the Potential Value of Coenzyme Q10 in Oxidative Stress: Enlightenment From a Synthesis of Clinical Evidence Based on Various Population - Zhang, Yili; Huang, Xinyi; Liu, Ning; Liu, Mengmin; Sun, Chuanrui; Qi, Baoyu; Sun, Kai; Wei, Xu; Ma, Yong; Zhu, Liguo (Frontiers in Pharmacology, 2022)
Background Oxidative stress (OS) is associated with ferroptosis. Coenzyme Q10 (CoQ10), as an adjuvant treatment, has shown to be beneficial against OS. However, the efficacy of CoQ10 as a therapeutic agent against OS has not been promptly updated and systematically investigated. Methods A systematic literature search was performed using the Medline, EMBASE, Web of science, Cochrane Central Register of Controlled Trials, CNKI, CBM, Science direct and clinical trial. gov to identify randomized clinical trials evaluating the efficacy of CoQ10 supplementation on OS parameters. Standard mean differences and 95% confidence intervals were calculated for net changes in OS parameters using a random-effects model. Results Twenty-one randomized clinical studies met the eligibility criteria to be included in the meta-analysis. Overall, CoQ10 supplementation increased the levels of antioxidant enzymes [including superoxide dismutase (SOD) (SMD = 0.63; 95% CI:0.38 to 0.88; P＜0.001), catalase (CAT) (SMD = 0.44; 95% CI:0.16 to 0.72; P=0.002)] significantly and the levels of malondialdehyde (MDA) (SMD = -0.68; 95 % CI: -0.93 to -0.43; P＜0.001) was decreased considerably. However, significant associations were not observed between this supplement and total antioxidant capacity (TAC), glutathione peroxidase (GPx) activity. Conclusion CoQ10 can improve OS as indicated by statistical significance in CAT and MDA concentrations, as well as SOD activity. Future studies focusing on long-term results and specific valuation of OS parameters are required to confirm the efficacy of CoQ10 on OS. We also believe that with the further research on ferroptosis, CoQ10 will gain more attention.